Extracellular vesicles produced by bone marrow mesenchymal stem cells overexpressing programmed death‐ligand 1 ameliorate dextran sodium sulfate‐induced ulcerative colitis in rats by regulating Th17/Treg cell balance through PTEN/PI3K/AKT/mTOR axis. Issue 12 (25th September 2022) - He, Hongxia; Chen, Qianyun; Fan, Heng; Leng, Xue yuan; Zhu, Feng; Gao, Fei; Zhou, Qiaoli; Dong, Yalan; Yang, Jia
Abstract: Background and Aim: Programmed death‐ligand 1 (PD‐L1) was involved in regulating Th17/Treg cell balance in ulcerative colitis (UC). Extracellular vesicles (EVs) from genetically modified bone marrow mesenchymal stem cells (BMSCs) can serve as a stable delivery system to overexpress PD‐L1. The study was designed to evaluate the therapeutic mechanism of BMSC‐EVs overexpressing PD‐L1 (PD‐L1‐EVs) on ulcerative colitis. Methods: Experimental model of UC was established in rats by drinking 5% dextran sulfate sodium (DSS). Apoptosis‐related proteins, inflammatory response‐related factors and oxidative stress related mediators were detected. Westernblot was used to detecte key proteins in the PI3K/AKT signaling pathway and its downstream effectors. The CD4 + Foxp3 + Treg cells and CD4 + IL‐17A + Th17 cells in spleen and mesenteric lymph nodes (MLNs) was detected by flow cytometry. Results: PD‐L1‐EVs significantly alleviated the manifestations and pathological damage of UC rats by inhibiting the expression of IFN‐γ, IL‐1β, IL‐8, IL‐6, IL‐2, BAX, NF‐κB, TNF‐α, MPO, and MDA, and up‐regulating the expression of IL‐4, BCL‐2, SOD, and GSH. Furthermore, the proportions of Th17 cells were decreased and that of Treg cells were upregulated by PD‐L1‐EVs treatment. PTEN inhibitors (bpv) partially abolished the inhibitory effect of PD‐L1‐EVs on PI3K‐AKT signaling and impaired the therapeutic efficacy of PD‐L1‐EVs. Conclusions: PD‐L1‐EVs mitigated colonal inflammation, apoptosis and oxidative stress through blocking the activation of PI3K/Akt/mTOR pathway and regulating the balance of Th17/Treg cells.